Selection of suitable materials for the development of an innovative thermochromic Trombe wall. Issue 2 (4th March 2021) - Perez, Gloria; Allegro, Virginia R.; Alonso, Carmen; Martín-Consuegra, Fernando; Oteiza, Ignacio; Frutos, Borja; Guerrero, Ana
ABSTRACT: An innovative system based on the Trombe Wall concept is under development to improve energy efficiency in buildings in different climatic conditions. The system takes advantage of the variable optical properties of a thermochromic mortar coating on the façade to optimize thermal behaviour. The mortar is based on the addition of organic thermochromic pigments to the cementitious matrix and is characterized by a high solar reflectance for temperatures higher than a nominal colour change value (Tc) and a low solar reflectance for lower temperatures. Materials potentially useful for this innovative system were analysed in this work. As prepared thermochromic mortar specimens, mortar specimens coated with different UV protecting products and mortar specimens covered by filter glasses with different optical responses were exposed to controlled outdoor environmental conditions during several days. Surface and environmental temperatures were monitored during the experiment. Moreover, reflectance spectra of the samples were recorded every day early in the morning, when the environmental temperature is significantly lower than Tc, and in the afternoon, when it is significantly higher than this value. Most suitable materials for the intended application were defined from an analysis of the optical and thermal properties of these specimens and their durability.